Radiation Biomarkers : Applications in Triage Management of Radiation Victims - Mishra, Saurabh; Kumar, Raj (Defence Life Science Journal, 2017)
Human exposure to ionizing radiation disrupts normal metabolic processes in cells and organs by inducing complex biological responses that interfere with gene and protein expression. Conventional dosimetry, monitoring of prodromal symptoms and peripheral lymphocyte counts are of limited value as organ- and tissue-specific biomarkers for personnel exposed to radiation, particularly, weeks or months after exposure. Analysis of metabolites generated in known stress-responsive pathways by molecular profiling helps to predict the physiological status of an individual in response to environmental or genetic perturbations. There is a need for research to rapidly determine an individual’s absorbed dose and its potential health effects after a potential radiological or nuclear event that could expose large portions of a population to ionizing radiation. Studies on biomarker identification after radiation exposure could contribute in biodosimetry, identifying individual dose absorbed, as well as biologic response, and administering immediate and proper medical care. In the recent scenario development of biomarker is major thrust area. In the present review paper articles related to gene biomarker, protein biomarker and metabolic biomarker are reviewed in order to sketch an overview on the recent advances related to developing an biomarker to assess the radiation induced toxicity.